OS DESAFIOS ENFRENTADOS PELO PROFESSOR DE CIÊNCIAS PERANTE DIFICULDADES DE LEITURA E ESCRITA NO 6º ANO - BRAGA, Ana Luiza Mar (2024)
Comprehension, reading and interpretation of texts, as well as writing control are essential processes for cognitive development. However, many children start higher Elementary School with worrying rates in terms of reading and writing. This interferes, consequently, in the teaching-learning process, since the minimum understanding and writing of a text is of paramount importance in the pedagogical context and contributes significantly to the student's academic success. In this way, this research moves in this problematic field, with the objective of promoting reflection on the challenges that the science teacher faces with students with delay in reading and writing, emphasizing the 6th year of Elementary School. Questioning and analyzing the teaching strategies and practices carried out by the teacher in facing this problem, mainly in the development of Science content. In this context, the research is the result of Supervised Internship II and is based on observations made in Science classes and on an interview with the teacher responsible for the 6th grade classes, which allowed highlighting difficulties faced daily in their classes. Therefore, it is clear that there are still serious problems with literacy, highlighting the need to apply methodological strategies to minimize the problem, as well as specific assessment devices that make it possible to circumvent the difficulties faced by students with reading and writing.